Hubungan Dukungan Keluarga dengan Capaian Imunisasi Dasar pada Anak Usia 9-24 Bulan - Khaira, Annisa Nabila; Dariani, Lili; Murni, Hasrah (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2025)
Immunization in Indonesia has reduced the incidence of dangerous diseases, but the coverage of complete basic immunization (IDL) is still below the national target of 90%, especially in West Sumatra Province. Reducing infant and child mortality remains a major challenge, where family support plays an important role in the success of immunization. This study aims to determine the relationship between family support and basic immunization coverage in children aged 9–24 months in the working area of the South Batipuh Community Health Center in 2025. This study uses a quantitative approach with a cross-sectional design conducted from January to June 2025. The study population consisted of 111 respondents, and 50 samples were obtained using the Lameshow formula. The sampling technique was Multistage Random Sampling with two selected villages, namely Padang Laweh and Guguak Malalo. Data were collected through interviews using questionnaires about family support and documentation studies of KIA books to see the completeness of basic immunization. Data analysis was performed univariately and bivariately using the Chi-Square test (α=0.05). The results showed that 52% respondents did not receive family support and 58% of children had not been fully immunized. A p-value of 0.002 indicated a significant relationship between family support and basic immunization coverage. The study showed that family support affects basic immunization coverage in children aged 9-24 months in the working area of the South Batipuh Community Health Center.